1997
DOI: 10.1046/j.1365-2141.1997.4373247.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage in CD34+ myelodysplastic cells is associated with intracellular redox changes and elevated plasma tumour necrosis factor‐α concentration

Abstract: Summary.Ineffective haemopoiesis in the myelodysplastic syndromes (MDS) is mediated, at least in part, by apoptosis, though the mechanisms of apoptotic induction are unclear. Tumour necrosis factor-a (TNF-a) promotes apoptosis via intracellular oxygen free radical production, oxidation of DNA and proteins, and is increasingly implicated in the pathogenesis of MDS. Using single-cell gel electrophoresis, we have identified oxidized pyrimidine nucleotides in the progenitor-enriched bone marrow CD34 þ compartment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 21 publications
2
58
0
1
Order By: Relevance
“…41 The physiological significance of TNF-␣ in MDS is supported by several lines of investigation: (1) enhanced in vitro formation of CFU-GM by antibody neutralization of TNF-␣ in MDS but no effect on AML CFU; 42 (2) inverse correlation between serum TNF-␣ concentration and hemoglobin in one study; 34 (3) inverse correlation between clinical response to erythropoietin and TNF-␣ levels; 35 (4) inverse correlation between a platelet response to IL-3 therapy and TNF-␣ serum levels; 13 (5) positive correlation between TNF-␣ producing cells in the marrow and apoptosis; 44 and (6) correlation between plasma TNF-␣ concentration with nucleotide oxidation in marrow MDS CD34 + cells. 45 This model suggests that secretion of TNF-␣ or other proapoptotic cytokines plays a pivotal role in the ineffective hematopoiesis of MDS, but the relationship to disease progression remains ill defined. This implies that strategies which effectively neutralize TNF may inprove hematopoiesis.…”
Section: Leukemiamentioning
confidence: 99%
“…41 The physiological significance of TNF-␣ in MDS is supported by several lines of investigation: (1) enhanced in vitro formation of CFU-GM by antibody neutralization of TNF-␣ in MDS but no effect on AML CFU; 42 (2) inverse correlation between serum TNF-␣ concentration and hemoglobin in one study; 34 (3) inverse correlation between clinical response to erythropoietin and TNF-␣ levels; 35 (4) inverse correlation between a platelet response to IL-3 therapy and TNF-␣ serum levels; 13 (5) positive correlation between TNF-␣ producing cells in the marrow and apoptosis; 44 and (6) correlation between plasma TNF-␣ concentration with nucleotide oxidation in marrow MDS CD34 + cells. 45 This model suggests that secretion of TNF-␣ or other proapoptotic cytokines plays a pivotal role in the ineffective hematopoiesis of MDS, but the relationship to disease progression remains ill defined. This implies that strategies which effectively neutralize TNF may inprove hematopoiesis.…”
Section: Leukemiamentioning
confidence: 99%
“…In line with this hypothesis, Peddie et al [17] have demonstrated the presence of oxidative damage and a reduction in intracellular glutathione (GSH) in MDS CD34+ cells, and a number of in vitro studies have shown the ability of the antioxidant thiol N-acetylcysteine (NAC) to reduce the apoptosis induced by free radicals in neuronal and leukemic cell lines by increasing the supply of intracellular GSH [18][19][20]. NAC also acts as an antiapoptotic agent by inhibiting TNF-a release from lymphocytes and accessory cells [21].…”
Section: Introductionmentioning
confidence: 78%
“…Amifostine treatment restored normal levels of apoptosis in our four cases with a high AI, and apoptosis levels remained in the range of values found in healthy subjects throughout all the courses of therapy, without concomitant increase of the blastic population, even in cases with excess of blasts. This biological effect is probably caused by the antioxidant property of amifostine, as enhanced susceptibility to oxidative stress may be one of the mechanisms of induction of the premature apoptosis of the dysplastic clone (Peddie et al, 1997), and by the concomitant above-mentioned inhibition of blast cell proliferation. It may explain the partial recovery of effective haematopoiesis with consequent improvement of peripheral cytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that high levels of apoptosis may be responsible for the ineffective haematopoiesis that characterizes MDS; various oncoproteins and cytokines may be involved in the regulation of this phenomenon, through the liberation of intracellular free radicals (Peddie et al, 1997;Yoshida & Mufti, 1999;Parker et al, 2000;Invernizzi et al, 2001). Thus, the reduction of apoptosis levels could be an important goal in the treatment of low-risk MDS.…”
mentioning
confidence: 99%